Parent-adolescent conflict and general health of 14-year-old adolescents in Behbahan, Iran - Mohammad Hossein Kaveh; Fatemeh Shirdel; Abdolrahim Asadollahi (Shiraz University of Medical Sciences, 2018)
Evidence suggests that the quality of family relationships is associated with family members' general health. Given of the scanty studies on adolescents, especially in Iran, this study aimed to determine the association between parent-adolescent conflict and adolescents' general health. Methods: Out of 40 high schools in Behbahan, 10 were randomly selected, and then 391 students were selected through random sampling method. The Parent-Adolescent Conflict Questionnaire and General Health Questionnaire were used for data collection. Pearson correlation coefficient, t-test, and ANOVA were used for data analysis in SPSS. Results: The findings of this study showed a significant and positive correlation between parent-adolescent conflict and general health (p=0.001, r=0.142). There was also a significant difference between the parent-adolescent conflict and mother's educational level (p=0.001), between general health and mother's educational level (p=0. 01), and between parent-adolescent conflict and father's educational level (p=0.003). There was no statistically significant difference between gender and parent-adolescent conflict and general health. Conclusion: According to the results, with an increase in parent-adolescent conflict, the general health scores would also increase, indicating lower general health. Further studies are recommended to identify familial conflict and general health (mental) risk factors. A family-oriented training program is recommended to improve the parent-adolescent communication skills